1988
DOI: 10.1128/jb.170.2.605-610.1988
|View full text |Cite|
|
Sign up to set email alerts
|

Instability of rRNA operons in Bacillus subtilis

Abstract: Many laboratory strains ofBaciUus subtilis contain 9 rather than 10 rRNA operons due to deletions occurring within the rrnj-rrnW or rrnl-rrnH-rrnG gene cluster. These operons are members of two sets of closely spaced clusters located in the cysA-arol region. Analysis of rescued DNA from integrants with insertions into rrnG and rrnH indicated that these tandemly arranged operons allowed frequent deletions of an rrn operon equivalent. These events may arise spontaneously by intrachromosomal recombination or by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 14 publications
2
62
1
Order By: Relevance
“…Some laboratory strains of B. subtilis contain only nine rrn operons due to spontaneous deletions within rrnW, H or G (Widom et al, 1988). This indicates that these operons are dispensable for growth in B. subtilis in the presence of the other rrn genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some laboratory strains of B. subtilis contain only nine rrn operons due to spontaneous deletions within rrnW, H or G (Widom et al, 1988). This indicates that these operons are dispensable for growth in B. subtilis in the presence of the other rrn genes.…”
Section: Resultsmentioning
confidence: 99%
“…In general, organisms that possess multiple rrn operons are considered to be able to grow faster than those that possess one or two operons. However, it is possible to delete one rRNA operon in either E. coli or B. subtilis without having a major effect on cell growth rate or physiology (Ellwood & Nomura, 1980;Widom et al, 1988), which suggests that the full number of copies of the rRNA operon is not required for rapid growth in these two organisms. Instead, it is assumed that many prokaryotes evolved multiple rRNA operons to cope with a variety of environmental conditions (Condon et al, 1992(Condon et al, , 1995.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of a single rrn operon has been reported to have little effect on cell growth rates or physiological processes in either E. coli or B. subtilis (Ellwood & Nomura, 1980;Widom et al, 1988). Asai and co-workers observed reduced growth rates in E. coli strains in which the number of rrn operon copies was reduced from seven to five (Asai et al, 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…Restriction map analysis of one such B. subtilis laboratory strain showed that homologous recombination between closely linked multiple rrn loci caused deletion of one of the loci and the loss of genetic material lying between the recombining rrn loci (375). A sequence of programmed deletions has been described for Anabaena heterocyst formation.…”
Section: Rearrangementsmentioning
confidence: 99%